Comportamento do equilíbrio simpato-vagal durante o treinamento de tiro com cadetes policiais militares - Boçon, Marilys (2019)
The police officer constantly faces violence and risk of death, thus working in an environment under pressing conditions. In order to perform properly, a police officer training must reflect the specificity of their duties. Shooting training is capable to provide a warlike realism, exposing their bodies to physiological changes. Such changes are an answer from the Autonomic Nervous System to both external and internal stimuli. Autonomic Nervous System modulation happens through the balance between actions of the Sympathetic Nervous System and the Parasympathetic Nervous System. The Autonomic Nervous System answers can be monitored through the behaviour of the Heart Rate Variability, a simple and non-invasive physiological marker of the autonomic cardiac impulses. Therefore, the aim of this study was to analyze the behaviour of Heart Rate Variability changing patterns before and after a shooting training session of cadets from the 1st year and 3rd year of Officials Graduation Course in Paraná. The study was conducted with 48 cadets, being 15 from the 1st year (26,8±4,9 years) and 33 from the 3rd year (25,6±3,9 years). Data was analyzed via IBM SPSSTM software, version 21.0. The Shapiro-Wilk normality test was conducted to verify symmetric and asymmetric distribution. In order to compare data from both 1st and 3rd-years groups the Mann Witney test was used. Absolute and relative frequency and qui-square test were used to find different proportions. To all statistic data the significant value of p<0,05 was applied. Results obtained in median in the 1st-year group to the MeanRR, SDNN, rMSSD, pNN50 and LF/HF ratio parameters were, respectively:613ms; 159,9ms; 161,5ms; 68% and 0,5 before the shooting session. After the shooting session the values were 615ms; 76ms; 21ms; 9% and 1,1 respectively. The 3rd -year group showed values of 873ms; 140ms; 71ms; 38% and 0,96 before and 945ms; 167ms; 106ms; 53% and 0,71 after. Results show higher Heart Rate Variability values for the 3rd-year group. It was concluded that possibly the longest period of stay in the Officials Graduation Course of the Cadets of the 3rd year promoted positive cardiac adaptations in the sinus node.